UPAYA PREVENTIF PEMERINTAHAN KABUPATEN ROKAN HILIR DALAM MENANGANI KEBAKARAN HUTAN DAN LAHAN PADA TAHUN 2012-2013 - Hamrizan "; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Preventive interpreted as deliberate attempt that is made to prevent disturbance, damage, or loss to person or society. While preventive efforts the government of Rokan Hilir regency in handdle land and forest fires in the year 2012-2013 were: (1) Creating policy of opened forest and without burning (zero burning). (2) sosialization the prohibition of open forest and land without burning by making props, posters, banners, warning signs, and others. (3) building block channels in each region or district that are prone to forest and land fire. (4) Make map or location are as prone to forest and land fires. (5) making instutional or organizational Concerned Citizens Fire (CCF) from the district to the village level. (6) Public participation in preventing forest and land fire. (7) Following the companies and the people who do the burning of forests and land. (8) Increasing survey activities againstt forest clearing and land.Keywords: Effort, Preventive, Government, Handle, Fire, and Forest